Fauna anofélica da área de construção da barragem da Usina Hidrelétrica Amador Aguiar I, na Bacia do Rio Araguari no município de Uberlândia, MG - Ferrete, Jaqueline Aida (2009)
Malaria is one of the infectious-parasitical diseases, which has been the cause of the majority of problems to public health in the world. The infectious agent is transmitted when a mosquito of the Anopheles gender bites human beings. The objective of this work is to demonstrate Anopheles fauna as well as the environment changes from May 2003 to December 2006 in the area of construction of a dam of the hydroelectrical generating plant Amador Aguiar I, located in the basin of the Araguari River in Uberlândia, Minas Gerais. The period was prior to the construction and extended through the construction period and the next year when of the formation of the lake. Four points were selected for capturing the mosquitoes, being one in the Araguari river bank and the other the control point , 184m far from the river bank. The work was accomplished from May 2003 to December 2006, with a total of 74 captures in 288h of field work and 1500h of laboratory work. Shannon traps, were used for the capture being captured 76 mosquitoes, of 09 species: one male and 75 females. The largest number was of Anopheles darlingi with 21 samples (27,6%), 13 samples of An. lutii (17,1%), 12 samples of An. evansae (15,8%), 12 samples of An. argyritarsis (15,8%), 07 samples of An. oswaldoi (9,2%), 04 samples of Anopheles sp. (5,3%), 03 samples of An. albitarsis (complex) (3,9%), 02 samples of An. triannulatus (2,6%), 01 sample of An. benarrochi (1,3%) and 01 sample of An. lanei (1,3%). From a total of 76 species, 38 (50%) were captured in the stage prior to the environmental changes (first stage), 21 (27,6%) in the stage in which the changes occurred (second stage) and 17 (22,4%) in the stage in which the lake was formed (third stage). In order to observe the insects behavior, captures of 12h were accomplished. They started at 6:00 p.m. and finished at 6:00 a.m. of the next morning. The collection was done in four periods of the year: cold-dry, warn-dry, warm-rainy, and cold-rainy period. Taking into consideration the amount of mosquitoes captured in the three stages of this research in the area of construction of the e, it becomes necessary that a constant monitoring should be done during some years, by means of a system of Entomological Surveillance in order to propose preventive measures of Health Environmental Surveillance due to human presence both in Vida Nova Settlement and tourists so that a Malaria outbreak can be avoided.